CRIAÇÃO DE CODORNAS PARA PEQUENOS PRODUTORES: DIVULGAÇÃO REMOTA - SILVA, Fabiana Teodózio da; SANTOS, Tânia Mara Baptista dos; CORREA, Jonas de Sousa; SANTOS, Marrony Gonçalves Pires dos (ANAIS DO ENIC, 2022)
-